Evaluation of degradation of organophosphate insecticide residues in stored corn (Zea mays L.) grains - Strada, Julieta (2021)
Fil: Strada, Julieta. Instituto Nacional de Tecnología Agropecuaria (INTA). Centro Regional Córdoba. Estación Experimental Agropecuaria Manfredi; Argentina.